Perkembangan Desa Wisata Lekuk 50 Tumbi Lempur Kabupaten Kerinci (2015-2020) - Irvan Toni; Zusmelia Zusmelia; Refni Yulia (Galanggang Sejarah, 2021)
Lempur Village is located in Gunung Raya District which has the potential of abundant natural resources and a beautiful atmosphere, on the other hand, the majority of Lempur Village people work as farmers. In 2014 Lempur Village was an ordinary village just like other villages, the community was still not aware that the potential possessed by the village could be developed and become a tourist attraction so that it could create jobs for the local community. With abundant natural potential and complete with hills, mountains, waterfalls, lakes, flora, and fauna, it should be able to attract tourists to come. Research Objectives To describe the development of the Lekuk 50 Tumbi Lempur Tourism Village in Kerinci Regency 2015-2020, especially in the physical field and to describe the socio-economic impact of the development of the Lekuk 50 Tumbi Lempur Tourism Village on the Lempur community before and after the establishment of the tourist village. The method used in this historical research consists of 4 stages, namely: Heuristics, Source Criticism, Interpretation, and Historiography. The research results of Development Lekuk 50 Tumbi Lempur Tourism Village have made many good contributions to the community. One of them is the formation of job vacancies such as Travel Agent, Porter, Cafe. Most of the people who feel the economic impact of the development of the Lekuk 50 Tumbi Lempur Tourism Village are traders, including meatball, satay, chicken noodle, and even cafe traders. The social impacts of the development of tourist villages on the community are: The majority of people are starting to become aware of the cleanliness of the surrounding environment, the re-activation of art studios in the community, the culture of the Lempur Village community is starting to be known to people outside the area such as Tauh Dance.